Seroprevalence of Bluetongue and associated risk factors in Costa Rican sheep flocks - Dolz, Gaby (2015)
A total of 359 sheep samples from 15 farms were analyzed for the presence of antibodies against bluetongue virus (BTV) by commercial enzyme-linked immunosorbent assay (ELISA). Antibodies were detected in 290 sheep from fourteen different flocks, distributed in all analyzed regions (Central, Chorotega, Atlantic Huetar, North Huetar, and Central Pacific) determining regional seropositivity between 63.5% and 100.0%, as well as an overall prevalence of 80.8 %. The within flock seropositivity percentages ranged between 28.6% and 100.0%. Two management practices were determined as risk factors for BTV seropositivity: buying animals, embryos, or semen from other farms without any sanitary control (59.1% of the participating farms, OR= 2.54; IC= 1.49 to 4.35), and the lack of quarantine areas or separated boxes for sick animals in each flock (70.47% of the studied flocks, OR= 6.47; IC= 3.68 to 11.40). All seronegative individuals (19.2%) came from flocks that used partial stabling, indicating this management practice as a protective factor (OR= 1.10; IC= 1.06 to 1.14) for BTV infection. Flocks with the highest seropositivity were found in low altitude regions close to the coast. The results of this study indicate that BTV is endemic in sheep herds from Costa Rica, and animals seem not show clinical signs. Further epidemiological studies are required to determine serotypes present in cattle, wild and small ruminants.